The relationship between isokinetic knee strength and knee biomechanics during single leg landing among recreational athletes - Shamsuri, Mohd Hafiz (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Objective: This study investigated the relationship between isokinetic knee strength and knee biomechanics during single leg landing among recreational athletes. Methods: 10 male recreational athlete from Universiti Sains Malaysia with mean age of 20 were recruited in this study. Participant go through a physical check up, which include measuring height, weight, body fat percentage, length of leg segment and their dominant leg. Next, participant’s isokinetic knee strength for both legs will be evaluated by using dynamometer. Next, participant have to execute counter movement jump with both leg as high as possible without any assistance and after that you need to land with dominant leg on the platform. Correlation were used for statistical analysis.